A decade of change: tuberculosis in England and Wales 1988–98. Issue 9 (22nd August 2003) - Balasegaram, S; Watson, J M; Rose, A M C; Charlett, A; Nunn, A J; Rushdy, A; Leese, J; Ormerod, L P
Abstract : Tuberculosis cases in children (aged under 15 years) in the National Surveys rose from 308 (rate: 3.3 per 100 000) in 1988 to 408 (4.2 per 100 000) in 1993 and then fell to 364 (3.6 per 100 000) in 1998. The rates in white children were 1.6, 2.0, and 1.1 per 100 000 respectively; in Indian subcontinent children, the rates were unchanged between 1988 and 1993 at around 33 per 100 000 but fell to 23 per 100 000 in 1998. In black African children, the rates were 15, 34, and 71 per 100 000 respectively. From 1988 to 1998, the proportion of cases resident in London more than doubled to 49% (rate: 11.9 per 100 000) and the proportion of cases in children born abroad increased from 13% to 27% in the country as a whole. Although the overall rate of tuberculosis in children in England and Wales has changed little between 1988 and 1998, the distribution of disease has changed in line with the change in adults. Services for the diagnosis and treatment of tuberculosis in children should be adapted to the changing pattern of disease in this group. Continuous enhanced tuberculosis surveillance will enable more detailed and timely scrutiny of trends in tuberculosis in the future.